DEVELOPING HOTS-BASED OPEN ENDED TEST ON GEOMETRY FOR JUNIOR HIGH SCHOOL - nurhayati nurhayati; Sugiatno Sugiatno; Silvia sayu (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims to develop HOTS-based open ended questions on Geometry material in junior high schools that are standardized based on the criteria of validity, reliability, level of difficulty, and discriminatory power. This research uses Research and Development research type. The research model is modified from the McIntire & Miller model. The research subjects were class VII students at SMP Negeri 2 Pontianak. The instruments used in this research are validation sheets and documentation. Data analysis techniques were carried out quantitatively and qualitatively. Based on the results of the research and discussion it can be concluded that the development procedure includes: 1) defining the test universe, audience, and purpose; 2) developing a plan; 3) conduct pilot test; 4) composing the test items; 5) validation the test; 6) complete the test. The development results obtained 15 item description questions with the results of the analysis including: 1) the reliability of the test was in the very high category, namely 0.95; the validity of the items in the average category is very high, namely 0.71; the average item difficulty level is in the moderate category, namely 0.45; and the discriminating power of the items in the average category is very good, namely 0.43.